Pengembangan PENGEMBANGAN MODUL PEMBELAJARAN SEPEDA LISTRIK SUNRACE UNIVERSAL 350 WATT - Apriadna, Alfath Maulana; Rabiman, Rabiman; Khaharsyah, Alfat (Jurnal Taman Vokasi, 2024)
This research aims to produce an electric bicycle learning module suitable for learning in the Motorcycle Technology Practice course at the PVTM study program of Sarjana Wiyata Tamansiswa University. The type of research used is R&D (Research and Development) with reference to the four-D model (define, design, develop, disseminate). The research site was carried out at Sarjana Wiyata Tamansiswa University and the research time was carried out from November 27 to December 4, 2023. The research subjects consisted of 2 expert validators of Mechanical Engineering Vocational Education, and respondents of 17 students in the Motorcycle Technology Practice (PTSM) course of Universitas Sarjana Wiyata Tamansiswa. This research data collection technique uses observation, interviews, and questionnaires. Quantitative descriptive analysis techniques. The results showed that: (1) The development of the 350 watt universal sunrace electric bike learning module had several steps, namely: (a) observation and interviews, (b) designing with module needs analysis, drafting, testing, validation, revision, (c) developing with module validation by media experts and material experts followed by revision, field trials on students, (d) disseminating bicycle modules electricity to PVTM students of Universitas Sarjana Wiyata Tamansiswa; (2) The feasibility assessment of material experts shows an average score of 90.25% and is included in the Very Decent category; Media expert raters showed an average score of 95.00% and were included in the Very Decent category; and (3) Student responses to the electric bicycle learning module showed an average score of 86.25% and entered the Very Decent category. Thus, the electric bike learning module developed can be categorized as Suitable for classroom or independent learning use. This is because the module can be used as a reference for teaching materials for PVTM students of Sarjana Wiyata Tamansiswa University as a reference in explaining electric bicycle learning materials at Sarjana Wiyata Tamansiswa University.